External Current Source–Based Unilluminated PV Partial Shading Emulation System Verified Through the Hybrid Global Search Adaptive Perturb and Observe MPPT Algorithm - Wang, Yidong; Yanarates, Cagfer; Zhou, Zhongfu (Frontiers in Energy Research, 2022)
PV array emulator has been a useful tool for testing PV inverters and MPPT algorithms employed in PV systems. This paper presents a novel PV array emulation system that was constructed by using unilluminated solar panels and external current sources, which has the same dynamic characteristics as actual PV array. By regulating the current from which the system fed by series-connected current sources, the proposed PV array emulation system can mimic the electrical characteristics of either series and parallel connected PV array under various solar irradiance and partial shading conditions. Detailed circuit connection and operational principle of the proposed PV array emulation system have been studied. Accordingly, the electrical characteristics of emulated PV system under various partial shading conditions were tested and analysed both theoretically and experimentally. In addition, a sophisticated hybrid global search adaptive perturb and observe (P&O) MPPT algorithm to test the feasibility of the emulation system has been presented. The proposed algorithm utilizes the global and local searching capability of the adaptive P&O algorithm with variable perturbation size. The performance verification of the designed algorithm has been validated using proposed emulation system, boost converter and dSPACE Real Time Interface (RTI) hardware. The results indicate that the proposed MPPT algorithm is effective in reducing power losses and faster in tracking speed of the maximum power point with less oscillation. Besides, excellent dynamic characteristics of the proposed emulator have been proved to be an ideal low-cost tool for testing PV inverters and various maximum power point tracking (MPPT) algorithms for commercial applications and university studies.